(untitled) (Journal of Computational Mathematics, 1998)
We examine a steady-state heat radiation problem and its finite element approximation in R^d, d=2, 3. A nonlinear Stefan-Boltzmann boundary condition is considered. Another nonlinearity is due to the fact that the temperature is always greater or equal than 0 [K]. We prove two convergence theorems for piecewise linear finite element solutions.